Penerapan Fuzzy Multi Criteria Decision Making untuk Menentukan Bibit Ikan Lele Unggul di Kabupaten Bandung - Nugroho, Abdul Hadi; Hidayah, Taufik; Nugraha, Dimas Adi; Marwondo, Marwondo (Masoem University, 2024)
The success of catfish cultivation is most influenced by the quality of the seeds. Proper selection of superior catfish seeds can increase crop yields and breeder profits. Seed selection needs to be assisted by the right decission making method. The aim of this research is to apply Fuzzy Multi Criteria Decision Making (FMCDM) in determining superior catfish seeds. Criteria for determining catfish seeds include growth rate, disease resistance, level of independence, seed size, and seed price. FCMC can support decision making for various criteria so that it can be used in determining superior catfish seeds. The research results show that FCMC can be used to determine superior catfish seeds. African catfish (clarias gariepinus) seeds were selected as superior seeds with the highest total score for each degree of optimism. At the optimization degree ? = 0, the total integral value reaches 0.349, at the optimization degree ? = 0.5, the total integral value reaches 0.417, and at the optimization degree ? = 1, the total integral value reaches 0.485, the highest compared to the other two seed variants. This research is useful in increasing catfish harvests, increasing profits for catfish farmers, and increasing the efficiency and effectiveness of catfish cultivation, especially in the Bandung Regency area.